The Socio-Economic Impact of the Community on Rammang-Rammang Tourism Development, Maros Regency - Nur amalia (Pustaka Digital Indonesia, 2023)
This study aims to determine the socio-economic impact of the community on the development of Rammang-Rammang tourism in Maros Regency. The type of research used in this research is descriptive qualitative, the method of collecting data is through observation, interviews, and direct documentation at the Rammang-Rammang tourist attraction, Maros Regency. The informants in this research are the community. The results of the study can be seen that tourism development has an impact on the community, namely tourism development is able to open up types of jobs for the community, tourism development increases people's income, and tourism development experiences changes in social values such as interactions, livelihoods, and people's lifestyles.